Layanan Bimbingan Klasikal Berbasis Psikoterapi Islam Untuk Meningkatkan Kontrol Diri: Studi Eksperimen pada Siswa MTs Al-Uswah Bergas Semarang - Khusnul Maqfiroh; Widayati Lestari; Wahidin Wahidin (Jurusan Tasawuf dan Psikoterapi Fakultas Ushuluddin, Adab dan Dakwah UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Self-control is a person's ability to control himself from various aspects such as behavior, feelings and ability to socialize in this case can be done by inculcating spiritual values, emotional mental and good morals in each individual. This study aims to determine the effectiveness of Islamic Psychotherapy-based Classical Guidance services to improve student self-control at MTs Al Uswah Bergas. The method used is quantitative using one group pre-test post-test by doing tests before and after the treatment is given. Data was collected through the distribution of questionnaires and subject documentation. The subjects in this study were students of class VIII MTs Al Uswah Bergas with a population of 124 students and a sample of 31 students. The data from this study were obtained with the help of SPSS for Windows Version 25.0. The results of this study indicate that prior to the implementation of Islamic psychotherapy-based classical guidance on self-control, students obtained an average of 86.97 or in the percentage of 58%, which means that they are in the low category. Meanwhile, after being given classical guidance services based on Islamic psychotherapy, the average score was 127.1 or in the percentage of 85%, which means that it is in the high category. This is evidenced by the simple paired t-test which obtained the value of sig. (2-tailed) of 0.000 < 0.05, so it can be concluded that the alternative is accepted.